Tuning Electrostatic and Hydrophobic Surfaces of Aromatic Rings to Enhance Membrane Association and Cell Uptake of Peptides. Issue 29 (25th May 2022) - de Araujo, Aline D.; Hoang, Huy N.; Lim, Junxian; Mak, Jeffrey Y. W.; Fairlie, David P.
Abstract: Aromatic groups are key mediators of protein–membrane association at cell surfaces, contributing to hydrophobic effects and π‐membrane interactions. Here we show electrostatic and hydrophobic influences of aromatic ring substituents on membrane affinity and cell uptake of helical, cyclic and cell penetrating peptides. Hydrophobicity is important, but subtle changes in electrostatic surface potential, dipoles and polarizability also enhance association with phospholipid membranes and cell uptake. A combination of fluorine and sulfur substituents on an aromatic ring induces microdipoles that enhance cell uptake of 12‐residue peptide inhibitors of p53‐HDM2 interaction and of cell‐penetrating cyclic peptides. These aromatic motifs can be readily inserted into peptide sidechains to enhance their cell uptake. Abstract : Substituents that increase hydrophobicity, electrostatic surface potential, polarizability and dipole moment of aromatic rings enhance binding to phospholipid bilayers and cell membranes, and increase peptide uptake into cells.